2002
DOI: 10.1152/ajprenal.00240.2001
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II induces apoptosis in rat glomerular epithelial cells

Abstract: ANG II has been shown to modulate kidney cell growth and contribute to the pathobiology of glomerulosclerosis. Glomerular visceral epithelial cell (GEC) injury or loss is considered to play a pivotal role in the initiation and progression of glomerulosclerosis. In the present study, we investigated the effect of ANG II on GEC apoptosis. Rat GECs were incubated with increasing doses of ANG II for variable time periods. Apoptosis was evaluated by cell nucleus staining and DNA fragmentation assay. ANG II induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
138
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(146 citation statements)
references
References 48 publications
5
138
0
3
Order By: Relevance
“…Plenty of studies have suggested apoptosis as the mainly mechanism contributing to podocyte loss. However, it should be noted that although there were numerous data demonstrating podocyte apoptosis in vitro studies 9, 10, the definite evidence for a primary role of apoptosis in either human or experimental DN is scant, and apoptotic cell death is rarely seen in diabetic glomeruli in situ 11, 12. There were also studies showing that apoptosis may only be a late consequence due to detachment or other podocyte dysfunction rather than a predominate initiator in podocyte loss 27.…”
Section: Discussionmentioning
confidence: 99%
“…Plenty of studies have suggested apoptosis as the mainly mechanism contributing to podocyte loss. However, it should be noted that although there were numerous data demonstrating podocyte apoptosis in vitro studies 9, 10, the definite evidence for a primary role of apoptosis in either human or experimental DN is scant, and apoptotic cell death is rarely seen in diabetic glomeruli in situ 11, 12. There were also studies showing that apoptosis may only be a late consequence due to detachment or other podocyte dysfunction rather than a predominate initiator in podocyte loss 27.…”
Section: Discussionmentioning
confidence: 99%
“…Singhal and colleagues (121) showed that angiotensin II (AngII) induces apoptosis in cultured rat podocytes. This effect was dose-and time-dependent.…”
Section: Apoptosismentioning
confidence: 99%
“…In cultured mesangial cells, Ang II [35][36][37] and aldosterone 38,39 provoke synthesis of extracellular matrix (ECM) proteins that accumulate in glomerulosclerosis. In podocytes, Ang II has been shown to induce apoptosis, 40,41 cytoskeletal rearrangement 42 and nephrin loss 43 in podocytes, alterations that have been linked to albuminuria. 44 Aldosterone can also damage podocytes by inducing apoptosis and reducing nephrin gene expression.…”
Section: Intrarenal Raasmentioning
confidence: 99%